O que se diz e o que se faz em nome da participação: Conselhão Santana do Acaraú-CE - Silva, Clódson dos Santos (2004)
The number of public management experiences in Brazilian cities that has been called “participative” (councils, participative budget, etc...) has grown in the last years. “Participation” has occupied more space in media, in political speeches, and in international multilateral agencies. However, overuse of this term caused the lack of any precise explicative content. There are so many social and political factions involved in these experiences that a detailed study of each specific case of the socalled “participation” is required. This work is about the case of Santana do Acaraú, an municipality localized in Ceará, a Brazilian state. The research locus is a council established in 1990, and popularly known as Conselhão (big council). I tried to avoid a close and rigid conception of participation, and adopted an interpretative perspective. “Participation” is understood in this dissertation as something that cannot be taken as given before real actions happen. The idea of participation here is an ethnographic one, that is, it is apprehended by the researcher in the field, with the observed group. People’s participation in the Conselhão is not due to an altruistic lack of rationality. There is an instrumental relationship between means and goals of different participants. I use these criteria to analyze other works whose authors used their own values to enunciate their diagnostics.